2020
DOI: 10.1016/j.tranon.2020.100871
|View full text |Cite
|
Sign up to set email alerts
|

The interaction mechanism between autophagy and apoptosis in colon cancer

Abstract: Autophagy and apoptosis play crucial roles in tumorigenesis. Recent studies have shown that autophagy and apoptosis have a cross-talk relationship in anti-tumor therapy. It is well established that apoptosis is one of the main pathways of tumor cell death. While autophagy can occurs in tumors with opposite function: protective autophagy and lethal autophagy. Protective autophagy can inhibit tumor apoptosis induced by anticancer drugs, while lethal autophagy can induce tumor cell apoptosis in cooperation with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
76
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 104 publications
0
76
1
Order By: Relevance
“… 22 Meanwhile, autophagy in CRC inhibited the tumor. 33 However, Zhang has found that autophagy plays a stimulative role in the development of CRC. 34 Meanwhile, autophagy can occur in tumors with the opposite function: protective autophagy and lethal autophagy.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Meanwhile, autophagy in CRC inhibited the tumor. 33 However, Zhang has found that autophagy plays a stimulative role in the development of CRC. 34 Meanwhile, autophagy can occur in tumors with the opposite function: protective autophagy and lethal autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, CPT exhibited obvious cytotoxicity on both HCT116 and SW620 cells while have no remarkable effects on SW480 cells, suggesting the selectivity of CPT treatment on CRC cells. Apoptosis is known as type I programmed cell death characterized by chromatin condensation, DNA fragmentation, and the formation of apoptotic bodies (Xie et al, 2020). Various pathways initiated by apoptosis lead to the cleavage of caspase-3, which leads to irreversible cell death (Xu et al, 2017;Xie et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is known as type I programmed cell death characterized by chromatin condensation, DNA fragmentation, and the formation of apoptotic bodies (Xie et al, 2020). Various pathways initiated by apoptosis lead to the cleavage of caspase-3, which leads to irreversible cell death (Xu et al, 2017;Xie et al, 2020). It has been reported by Xu et al that CPT induced the apoptosis in multidrug-resistant human CRC cells SW620 Ad300 (Xu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy is a stringently regulated process in which cellular debris, degenerated organelles, and aged proteins were wrapped by autophagosome and subsequently degraded by fusion of the autophagosome with lysosome [ 22 ]. Furthermore, a delicate balance usually exists between autophagy and apoptosis within the cell [ 23 , 24 ]. Therefore, we hypothesize that the downregulated expression of cathepsin proteins under PDR may reduce autophagic flux and promote apoptosis in the cell.…”
Section: Introductionmentioning
confidence: 99%